Translating the Takaful Islamic Insurance: An Analytical Approach (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
In the last decades, Muslim societies have experienced multiple processes of modernization, as an example, in the area of finance. This marked among other things, the rise of Islamic finance particularly Islamic insurance (takaful). As a consequence, the number of Muslim literates in finance has increased tremendously as well as the number of texts, concerning Islamic legal rulings on Islamic financial transactions which involve Islamic insurance engaged in these finances. At the same time, the Islamic insurance has been channeled to compete or totally eradicate conventional insurance in the new Muslim financial markets or at least in the Islamic countries, and these has triggered disputes among the scholars as to the viability and originality of the Islamic insurance. The disputes over the originality and viability of Islamic insurance to replace conventional insurance might contribute to the emergence, in the Muslim countries, of a tradition of scholarly debates that would stress re-evaluation and innovation of the existing body of knowledge.